Study on Green Energy Converter for the Purpose of Optimising Teaching and Learning in Energy Science - Alias, Azrul Nizam; Md Ab Lazis, Mardhiatul Najwa; Sugandi, Julyle Muhamad; Mohd Salman, Nurfasyarina Azureen; Mohd Khalid, Muhammad Hafiz; Julius, Rafael; Mohamad Sahapini, Noor Fadhilah; Yahya, Mohd Ashmir; Mahfodz, Zulfadli; Ramli, Fariesha Farha; Abdullah, Fathiah (UiTM Press, 2020)
Knowledge of energy conservation is vital to be understood by students in grasping the topic of energy science. Hence, a study has been piloted to produce energy converter which can be used practically by the students to understand about the conversion of energy from kinetic energy to electricity. In the convertible of kinetic energy to electrical energy, as these energy undergo conversion, the kinetic energy are stored in two forms of storage apparatus. The first type is synchronous flywheels which operate within the allowable range of the synchronous frequency. The second type is asynchronous flywheels whose rotational speed is independent from the system synchronous frequency and varied over a wide range and this features gives the asynchronous flywheel the ability to store and release significant amount of kinetic energy. The outcomes from this study displayed successful performance which is dynamo that act as generator for the converter as energy is being convert from the kinetic energy into the electrical energy and efficaciously can be used to charge electrical gadget.